2011
DOI: 10.1093/nar/gkr261
|View full text |Cite
|
Sign up to set email alerts
|

Genetically tagged TRE5-A retrotransposons reveal high amplification rates and authentic target site preference in the Dictyostelium discoideum genome

Abstract: Retrotransposons contribute significantly to the evolution of eukaryotic genomes. They replicate by producing DNA copies of their own RNA, which are integrated at new locations in the host cell genome. In the gene-dense genome of the social amoeba Dictyostelium discoideum, retrotransposon TRE5-A avoids insertional mutagenesis by targeting the transcription factor (TF) IIIC/IIIB complex and integrating ∼50 bp upstream of tRNA genes. We generated synthetic TRE5-A retrotransposons (TRE5-Absr) that were tagged wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…The “HindIII arm” was generated by amplification of nucleotides 1–1166 of the agnC gene including its authentic translation start codon. The pGEM-agnC-GA plasmid was linearized and transformed into D. discoideum AX2 or DH1 cells and transformants were selected in HL5 medium (Formedium, Hunstanton, UK) containing 6 μg/ml blasticidin (Life Technologies, Carlsbad, USA) [ 37 ]. From such clones genomic DNA was isolated and screened by PCR for insertion of the GA cassette at the targeted locus using one primer specific for the blasticidin resistance gene and a second primer that hybridized outside of the DNA sequences covered by the HindIII arm.…”
Section: Methodsmentioning
confidence: 99%
“…The “HindIII arm” was generated by amplification of nucleotides 1–1166 of the agnC gene including its authentic translation start codon. The pGEM-agnC-GA plasmid was linearized and transformed into D. discoideum AX2 or DH1 cells and transformants were selected in HL5 medium (Formedium, Hunstanton, UK) containing 6 μg/ml blasticidin (Life Technologies, Carlsbad, USA) [ 37 ]. From such clones genomic DNA was isolated and screened by PCR for insertion of the GA cassette at the targeted locus using one primer specific for the blasticidin resistance gene and a second primer that hybridized outside of the DNA sequences covered by the HindIII arm.…”
Section: Methodsmentioning
confidence: 99%
“…However, similar to Ty3 elements, mutations of the box B promoter that interfere with binding of TFIIIC abolish the targeting of TRE5-A to the tRNA target gene [ 133 ]. TRE5-A insertion profiling demonstrated that TRE5-A can also integrate at the Pol III-transcribed ribosomal 5S gene which is located on a multi-copy extrachromosomal DNA element harboring the rRNA genes [ 134 , 135 ]. Unlike TRE5, TRE3 has a broader range of insertion that is 40–150 bp downstream of tRNA genes in the same transcription orientation (Fig.…”
Section: Tes Target Rna Pol III Transcribed Genes In Dictyomentioning
confidence: 99%
“…By using a pre-defined integration site, the assay can analyze the structural requirements of genomic loci to be recognized by TRE5-A. The right part outlines the use of defined, genetically tagged TRE5-A retrotransposons 17 to determine the target site specificity of TRE5-A retrotransposons. Considering that TRE5-A bsr elements mimic the natural integration preference of endogenous TRE5-As, this assay can identify natural integration sites and determine the rate of off-site integrations.…”
Section: Genetically Tagged Tre5-as: Defining the Retrotransposon Strmentioning
confidence: 99%
“…This prediction would be supported by results showing that B boxes occur on the extrachromosomal DNA elements that carry the D. discoideum ribosomal tRNA genes. 17 Thus, it will be interesting to see if TRE5-A bsr elements will integrate at loci not associated with tRNA genes and whether these loci are off-site targets or previously unrecognized functional B boxes occupied by the TFIIIC/TFIIIB complex. If we predict that every authentic TRE5-A bsr integration difficult to estimate how frequently tRNA gene-specific integration events have occurred.…”
Section: Trna Gene-targeted Retrotransposition: Avoidingmentioning
confidence: 99%
See 1 more Smart Citation